Legal Protection Of Investors In Mutual Fund Investment - Sulaiman; Fijra Dwi Handini (Jurnal Hukum Volkgeist)
The development of digital technology and economic growth has encouraged the increasing interest of Indonesian people in investment, especially through online-based mutual funds. Mutual funds are attractive investment instruments because they are managed by professional investment managers, offer portfolio diversification, and have high accessibility. Nevertheless, this investment still carries risks, both from market fluctuations and potential abuse of authority by the manager, such as manipulation of financial statements. Therefore, legal protection for investors is an important aspect to create certainty and security in investing. This research aims to analyze the forms of legal protection available to mutual fund investors based on Indonesian laws and regulations, as well as identify legal remedies that can be taken in the event of losses due to negligence or fraud by investment managers. Through normative studies, it is found that although there are regulations governing investor protection, such as Law Number 8 of 1995 concerning Capital Markets, there is still a need to strengthen supervision and assertiveness in sanctioning to increase the effectiveness of such protection. This study emphasizes the importance of strengthening regulations and public education to encourage the growth of healthy, fair, and sustainable mutual fund investment in Indonesia.